Students’ Self-Efficacy in Learning English: A Case Study of Seventh-Grade Students at Mts Putri DDI Mangkoso - M, Ulfah Hani; Sunubi, Abdul Haris; Arqam, Arqam; Tjalla, Magdahalena; Dalle, Ambo (JELITA, 2026)
This study examines the impact of students’ self-efficacy on their performance in classroom English learning and identifies factors influencing the self-efficacy of seventh-grade students at MTs Putri DDI Mangkoso. Employing a qualitative case study design, data were collected through participant observation, semi-structured interviews, and documentation involving seven purposively selected students. Data were analysed using an interactive model consisting of data reduction, data display, and conclusion drawing/verification. The findings indicate that self-efficacy positively influences English learning performance; students with higher self-efficacy achieved better scores and demonstrated more active participation. Mastery experiences emerged as the strongest source of self-efficacy, followed by vicarious experiences through peer observation, verbal persuasion from teachers and peers, and physiological or emotional states such as speaking anxiety. Key challenges included fear of negative evaluation, limited English exposure beyond the classroom, and restricted access to authentic practice within the boarding school context. Strengthening self-efficacy through gradual success experiences, supportive classroom environments, constructive feedback, and emotional regulation is essential to enhance students’ motivation and performance. This study offers in-depth qualitative insights and practical implications for teachers and school administrators.